Efficacy and safety of paclitaxel drug-coated balloon angioplasty for stenosis of hemodialysis vascular access: 6-month results from a brazilian multicenter prospective study - Leonardo de Oliveira Harduin; Thiago Almeida Barroso; Julia Bandeira Guerra; Márcio Gomes Filippo; Leonardo Cortizo de Almeida; Carlos Alexandre Rosa Gama; Brunno Ribeiro Vieira; Renata Silveira Mello; Adriano Martins Galhardo; Jorge Paulo Strogoff-de-Matos (Jornal Vascular Brasileiro, 2025)
ABSTRACT Background Stenosis resulting from neointimal hyperplasia remains a significant concern associated with dysfunction of arteriovenous fistulas (AVF). Objectives To investigate the safety and efficacy of paclitaxel drug-coated balloon (DCB) angioplasty for treating failing AVFs. Methods Investigators analyzed 58 hemodialysis patients treated with RangerTM DCBs from December 2022 to December 2023 across four centers. Lesions treated were de novo or restenotic and located in the juxta-anastomosis, cannulation zone, and outflow segment. Patients were evaluated through physical examinations and Duplex ultrasound at 1, 3, and 6 months. The primary efficacy endpoint was target lesion primary patency at 1, 3, and 6 months, and the primary safety endpoint was freedom from serious adverse events through 30 days post-procedure. Secondary endpoints were access circuit primary patency and technical and procedural success. Results Nine patients (16%) had thrombosed access at the initial presentation, and 31 (53%) presented with recurrent stenosis. The target lesion primary patency rate at 6 months was 85.7%, and the access circuit primary patency rate at 6 months was 67.5%. No serious adverse events, either local or systemic, were reported. Sex, age, stenosis location, type of lesion, presence of thrombosis, lesion recurrence, diabetes status, or whether post-ballooning dilation was performed did not significantly affect the 6-month target lesion primary patency. Conclusions DCB angioplasty was shown to be safe and effective for treating peripheral stenosis in vascular access.